The Labor Market Integration of Syrian Refugees in Turkey - Murat Demirci; Murat G. Kirdar (Institute of Labor Economics (IZA), 2021)
Turkey hosts the largest population of refugees globally; however, we know little about their labor market outcomes at the national level. We use the 2018 round of the Turkey Demographic and Health Survey, which includes a representative sample of Syrian refugees in Turkey for the first time, to examine a rich set of labor market outcomes. We find that the native-refugee gap in men's employment in Turkey (in favor of natives) is much smaller than that reported for most developed countries. Moreover, men's employment peaks quite early (one year) after arrival and remains there, whereas women's employment is lower to begin with and changes little over time. Once we account for demographic and educational differences, the native-refugee gap in men's (women's) paid employment reduces to 4.7 (4.0) percentage points (pp). These small gaps conceal the fact that refugees' formal employment is much lower. Even after accounting for the covariates, refugee men's formal employment rate is 58 pp lower. In addition, the native-refugee gap is the smallest in manufacturing for men and in agriculture for women, and the gap is also much smaller in wage-employment than self-employment and unpaid family work for both genders. Young refugees are more likely to work than natives, whereas the gap favors natives among the prime-age working people. Moreover, the native-refugee gap in employment widens for more educated refugees. Finally, accounting for the differences in covariates, the native-refugee gap in men's employment vanishes for Turkish-speaking refugees but persists for Arabic- and Kurdish-speaking refugees.
Keywords: F22; J21; J61; O15; 330; Syrian refugees; labor market integration; employment; Turkey